ECO-FRIENDLY GREEN SYNTHESIS VERSUS CONVENTIONAL CHEMICAL METHODS OF NANOPARTICLES SYNTHESIS: IMPLICATIONS FOR BIOMEDICAL EFFICACY, SAFETY, AND APPLICATIONS - J, Sudhir; M, Sudharsun; Preethi, Jesia Persis; S, Sudha Srikesavan; S, Usha Nandhini (International Journal of Pharma and Bio Sciences, 2026)
Nanoparticles (NPs) have revolutionized the field of biomedicine, but their therapeutic potential critically depends on the methods used for their synthesis. Traditional chemical approaches, such as co-precipitation and sol-gel methods, allow precise control over NP size, shape, and crystallinity, making them highly effective and amenable to industrial-scale production. However, these methods often generate toxic by-products, utilize hazardous reagents, and consume significant energy, posing environmental and health risks. In contrast, green (biological) synthesis techniques employ eco-friendly reducing agents, including plant extracts, microorganisms, and bio-waste. This approach offers a safer, cost-effective, and environmentally sustainable alternative, providing improved biocompatibility and a better safety profile, largely due to natural bioactive surface-capping agents. This review compares conventional chemical and green synthesis methods of nanoparticles, evaluating their effects on physicochemical properties and biomedical performance. Additionally, it provides a detailed discussion of their applications in areas such as antimicrobial activity, drug delivery, and imaging, highlighting the superior safety and lower toxicity of green-synthesized NPs. Overall, despite the technical precision of chemical methods, green synthesis techniques demonstrate lower environmental impact, reduced toxicity, and enhanced safety, making them the most desirable and sustainable approach for developing nanoparticles for both biomedical and non-medical applications, including environmental remediation and sustainable agriculture.